Criteria and Diagnostic Assessment of Intercultural Communicative Competence Development Through English Folklore - Ranokhon Maxsudaliyeva (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
This study explores the development and diagnostic assessment of intercultural communicative competence through English folklore in foreign language teacher education. The research involved 366 third-year students enrolled in the course Methods of Teaching Foreign Languages at Namangan State Pedagogical Institute, Chirchik State Pedagogical University, and Fergana State University. An experimental instructional model integrating English folklore narratives and interactive intercultural learning strategies was implemented. Authorial diagnostic criteria were developed to assess intercultural competence, including cognitive-cultural awareness, interpretive competence, communicative adaptability, cultural empathy, and reflective intercultural sensitivity. The findings indicate that folklore-based instruction enhances students’ intercultural awareness, tolerance, and communicative flexibility, confirming its effectiveness as a methodological tool in teacher training.